Analysis on the Effectiveness of Speaking Class during Online Learning in COVID-19 Pandemic Period - Mouna Lidza (Universitas Serambi Mekkah, 2022)
The purpose of this study was to determine the effectiveness of learning English speaking skills online during the COVID-19 period, and whether there were any obstacles encountered in the implementation of online speaking skills teaching and learning during the COVID-19 period. This study used mixed method research with explanatory sequential design, in which collecting and analyzing the quantitative data was done in the first stage, followed by the qualitative data collection and analysis in the second stage. A questionnaire was given to 20 English department students of University of Serambi Mekkah from two different batches; year 2019 and year 2020. An interview was then conducted to verify the data and to validate the data. In general, almost all students stated that learning speaking skills online was not effective, and they experienced obstacles during the learning process which resulted in a decreased interest in learning.